Pendampingan Pengembangan Umkm Melalui Pemanfaatan Sumber Daya Alam Dan Pemberdayaan Sumber Daya Manusia Di Desa Ponggang Kabupaten Subang - Widawati, Enny; Sugioko, Andre; Bachtiar Wahju, Marsellinus; Sukwadi, Ronald; Antoni Hutahaean, Hotma; Triyanti, Vivi; Nguyen Thi Bich , Thu (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are vital business units in developing and growing the Indonesian economy. The people of Ponggang Village have the potential for their naturalresources, which can be processed to make a product that can make a steady income from MSMEs. This community service activity aims to open up insights and share the importance of entrepreneurship from an early age. The results obtained from this community service include the packaging of Ponggang Village MSME products with a unique design that has an element of identity from Ponggang Village MSME products, namely the